Pengembangan Model Pembelajaran Berbasis Deep Learning untuk Peningkatan Keterampilan Berbicara Peserta Didik SMP Muhammadiyah Purworejo - Joko Purwanto; Nurhidayati Nurhidayati; Umi Faizah; Inayatur Rifki; Dea Permataningtyas (Pusat riset dan Inovasi Nasional, 2025)
This study aims to describe the development of a deep learning-based learning model to improve the speaking skills of students at SMP Muhammadiyah Purworejo. This study uses research and development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research location was at SMP Muhammadiyah Purworejo in the 2024/2025 Academic Year for class VIII students with a population selection of class VIII students. Meanwhile, the research sample with a purposive sampling technique was 30 students representing diverse speaking abilities. Data were collected through tests, questionnaires, and observations. The test measures speaking skills, the questionnaire collects student responses, and the observation sheet observes the activities of teachers and students during the learning process. Interactive methods were used to analyze the data. The results showed an increase of 11.3 points in pretest data of 28.9 and posttest of 40.2. In addition, the questionnaire and observation showed that both teachers and students showed positive responses to the application of the deep learning model. Therefore, it can be concluded that students of Muhammadiyah Purworejo Middle School can acquire better speaking skills with this model.